Cryptosporidium sp. and Blastocystishominis Findings: A cross-sectional Study among Healthy Versus Immunocompromised Individuals - Masyithah Darlan, Dewi; Fakhrur Rozi, Muhammad; Argente Nurangga, Muhammad; Chotim Amsari, Lulu (International Journal of Psychosocial Rehabilitation, 2020)
Background: Cryptosporidium sp. and Blastocystishominis are widely recognized as opportunistic intestinal parasites among the general population, particularly immunocompromised individuals producing acute or chronic diarrhea. Nevertheless, B. hominis has still become dubious as its pathogenesis has not yet fully elucidated. Objective: The study aims to prove the classical findings of the theoretical background, whether or not Cryptosporidium sp. and B. hominis are associated with immunocompromised conditions. Materials and methods: The cross-sectional study enrolled 52 participants, then divided into two groups: HIV positive (29 patients) and healthy individuals (23 patients) who involuntarily provide their feces for microscopic parasitic examination in the Department of Parasitology, Faculty of Medicine, Universitas Sumatera Utara, Medan, Indonesia. All data were presented in bivariate mode to undergo further statistical analysis using the chi-square test. Results: There are descriptive findings proving that B. hominis is found mostly among HIV positive (7 samples), while only two positive samples are in the immunocompetent group, yet no significant association between the infection and HIV status has been obtained (p = 0.144; OR 0.299, 95%CI 0.056- 1.608). Similarly, it was also not statistically proven that Cryptosporidium sp. infection and HIV status have a significant relationship (p = 0.197; OR 4.20, 95% CI 0.407- 43.374). Conclusions: In addition to its uncertain pathogenesis, B. hominis still becomes a neglected parasitic infection among the HIV population, while Cryptosporidium sp. is confounded by other factors, mainly the CD4 count of each individual for the infection to occur.